Minimally invasive techniques in stage I–II chronic hemorrhoids: outcomes and prioritization - Bilianskyi, L. S.; Voloshyn, I. V. (General Surgery, 2025)
Various minimally invasive techniques are widely used in the treatment of stage I – II chronic hemorrhoids (CH), including rubber band ligation (RBL), transanal hemorrhoidal dearterialization (THD), laser vaporization (LV), among others. Bipolar vaporization (BPV) is a novel and promising method of thermal tissue destruction using the EK‑300M (Svarmed, Ukraine) bio‑welding generator. Its effectiveness compared to other techniques remains insufficiently studied. Objective – to compare the outcomes of treating complicated stage I – II CH using four minimally invasive techniques (BV, LV, THD, RBL) and to determine their priority ranking. Materials and methods. The study included 118 patients (67 men and 51 women, aged between 19 and 70 years; the mean age was 43.1±12.5 years) with symptomatic stage I – II CH resistant to conservative therapy. Patients were divided into four groups according to the applied method: BPV (n=32), LV (n=21), THD (n=23), and RBL (n=42). The following parameters were assessed: duration of the procedure, frequency of intraoperative complications, dynamics of symptoms (pain, prolapse, bleeding, itching, soiling), recurrence rate, and patient satisfaction at 12‑month follow‑up. Results. All techniques demonstrated an adequate level of effectiveness and safety. The 12‑month recurrence rates were BPV – 3.1%, LV – 4.8%, THD – 13%, and RBL – 26.2%. The highest satisfaction level (8 – 9 points) was observed in the BPV and LV groups (> 90% of patients). BPV and LV showed the best clinical efficacy and stability of outcomes. THD ranked third in terms of effectiveness, while RBL had the lowest priority due to the high recurrence rate. Conclusions. Considering clinical outcomes, availability, and cost, bipolar vaporization can be recommended as a priority method for the treatment of stage I – II CH. Further multicenter studies are needed to confirm its long‑term efficacy.